Interval linear programming for water quality management - Goh, Pricycia Mong Sei. (2011)
Water is a very vital resource in the world. Due to increasing globalisation, much of the water sources in the world have been polluted. In the world today, water quality management is essential in tackling the problem of water pollution. Water quality models were used to determine the degree of pollution in a water body. However, uncertainty is an inevitable property that exists in any systems and is an important factor in decision making process. Thus, it is an important consideration that decision makers have to take in. Water quality models also enables decision makers to judge the level of treatment required for their effluent discharge while meeting the environmental guidelines. In this study, Streeter-Phelps model and conventional non-linear optimization will be adopted to find the lowest cost of treatment subject to several constraints. With the introduction of a case study, the proposed methodology proved to be feasible in predicting the water quality as well as optimizing the cost and efficiency of treatment of different industries in a river segment.